2017
DOI: 10.1128/aac.01088-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Biofilm Dispersal as a Therapeutic Strategy To Restore Antimicrobial Efficacy

Abstract: As a proof-of-concept study, the direct impact of biofilm dispersal on the efficacy of imipenem and tobramycin was evaluated against 3-day-old biofilms of Arabinose induction of biofilm dispersal via activation of the phosphodiesterase YhjH in the engineered strain PAO1/p - resulted in increased antimicrobial efficacy and synergy of the imipenem-tobramycin combination. These results support the use of biofilm dispersal to enhance antimicrobial efficacy in the treatment of biofilm-associated infections, represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…In the present study, IPM was the most effective in S. putrefaciens and K. pneumoniae biofilm mass removal, however, total removal was not achieved, which is a critical aspect in biofilm control. In fact, antibiotics can promote significant killing of biofilm cells without causing their dispersal/removal ( Roizman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, IPM was the most effective in S. putrefaciens and K. pneumoniae biofilm mass removal, however, total removal was not achieved, which is a critical aspect in biofilm control. In fact, antibiotics can promote significant killing of biofilm cells without causing their dispersal/removal ( Roizman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, later investigations revealed that biofilm dispersal could induce by the availability of nutrient, oxygen limitations, and the presence of several chemicals 6 . New studies are beginning to address biofilm dispersal as a highly regulated active process for start of infection at new sites 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, typical in vitro studies suggest strategies to increase the efficacy of antibiotics against biofilms involves induction of biofilm dispersal 6 . This led to explore biofilm control by using dispersal in P. aeruginosa as well.…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of this study were to 1) assess the potential for synergy of the unconventional antimicrobial combinations and 2) evaluate the potential of c-di-GMP mediated biofilm dispersal to increase antimicrobial efficacy; against biofilms of colistin susceptible and resistant strains of P. aeruginosa. Dispersal of biofilm utilizing this specific cellular mechanism has proven to be a promising strategy to treat biofilms of susceptible strains (Roizman, Vidaillac et al 2017). The question here is whether this strategy is effective against biofilms of resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the publication "In-vitro evaluation of biofilm dispersal as a therapeutic strategy to restore antimicrobial efficacy" (Roizman, Vidaillac et al 2017).…”
Section: Dispersal As a Strategy To Restore Antibiotic Efficacymentioning
confidence: 99%